Anglican Cathedral of St. John the Baptist in St. John's - Squires, Allen; Squires, Pearl (1962)
Photograph of Andglican Cathedral of St.John the Baptist in St. John's. Labeled as "St. Paul's Cathedral" By Pearl Squires.